(untitled) (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2022)
An accounting information system is an organization of forms, records and reports that are coordinated in such a way as to provide financial information needed by the management of a company to facilitate management within a company. Accounting information systems include the use of information technology to provide information for users and management. PT Wahana Murni Plantation uses petty cash which must be recorded systematically and provides fast and accurate information to the petty cash manager. Besides that, the use of technology that is currently developing can save and provide data in real time to petty cash managers. This study aims to design a system that can assist in the management of petty cash funds which functions to carry out work activities very easily, such as recording cash flow transactions, submitting petty cash replenishment, and petty cash reports, all of which are made on a website with using the programming language PHP and MySQL as a database for its use.